Hybrid Differential Evolution Particle Swarm Optimization Algorithm for Reactive Power Optimization - Shouzheng Wang; Lixin Ma; Dashuai Sun (2010 Asia-Pacific Power and Energy Engineering Conference, 2010)
Reactive power optimization is a mixed integer nonlinear programming problem where metaheuristics techniques have proven suitable for providing optimal solutions. In this paper, swarm and evolutionary algorithm have been applied for reactive power optimization. The objective of this nonlinear optimization is minimization of system losses and improvement of voltage profiles in a power system. A hybrid differential evolution particle swarm optimization algorithm is presented to obtain the global optimum. The proposed algorithm is implemented on the IEEE 14-bus system. To validate the effectiveness of the algorithm, the simulation results are compared with other optimization algorithms'. It is shown that the approach developed is feasible and efficient.